A reinvestigation on the taxonomic identity of Rhynchospora panduranganii (Cyperaceae) - Deepu, S.; Thomas, William Wayt (Phytotaxa, 2019)
The taxonomic identity of Rhynchospora panduranganii and R. corymbosa (Cyperaceae) is resolved based on a detailed study of both herbarium specimens and living collections. We provide distinguishing characters of both species, along with photographs for easy identification.